The quantum leap in therapeutics for advanced ALK+ non-small cell lung cancer and pursuit to cure with precision medicine - Itchins, Malinda; Pavlakis, Nick (Frontiers in Oncology, 2022)
Since the discovery 15 years ago, we have seen a quantum leap in the treatment and survival for individuals diagnosed with ALK+ lung cancers. Unfortunately however, for most, the diagnosis is made in an incurable circumstance given the late presentation of symptoms. Through a revolutionary wave of therapeutics, individuals may remarkably live over a decade, however many fall short of this milestone, as the molecular profile of this disease is very heterogeneous, reflected in variable survival outcomes. Despite a significant improval in survival and quality of life with ALK-inhibitor monotherapies, now available across multiple-generations, drug resistance and disease relapse remains inevitable, and treatment is offered in an empiric, stepwise, non personalised biomarker informed fashion. A proposed future focus to treating ALK to improve the chronicity of this disease and even promote cure, is to deliver a personalised dynamic approach to care, with rational combinations of drugs in conjunction with local ablative therapies to prevent and constantly proactively alter clonal selection. Such an approach would be informed by precision imaging with MRI-brain and FDG-PETs sequentially, and by regular plasma sampling including for circulating tumour DNA sequencing with personalised therapeutic switches occurring prior to the emergence of radiological and clinical relapse. Such an approach to care will require a complete paradigm shift in the way we approach the treatment of advanced cancer, however evidence to date in ALK+ lung cancers, support this new frontier of investigation.